Use (POC) Of Rice Washing Water, Coconut Water, And Fermented Chicken Egg Shalls On The Density Of Chlorella Sp. Semi-Mass Scale - Ismail, Irwan; Lutur, Elen Marta; Irsan, Irsan (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
Chlorella sp. is one of the microalgae that is used as natural food because it contains more nutrients compared to artificial food. In order to obtain microalgae such as Chlorella sp. The aim of the cultivation process is to obtain microalgae in good condition, so that the availability of natural food can be fulfilled through the culture process. To support the culture process, organic materials are needed in the form of POC which are easy to find and of course naturally available. One example is the use of POC organic material which is produced from adding coconut water, rice washing water and chicken egg shells, then fermented using EM4. The aim of this research was to determine the effect of using liquid organic materials (POC) on the density of Chlorella sp. and the best concentration treatment during the long-term culture process. The research method applied was a Completely Randomized Design (CRD), including four treatments and three repetitions throughout the research. Chlorella sp cell density. The highest occurred in treatment K (control concentration 25 ml/container), then treatment B (concentration 200 ml/container), treatment A (concentration 100 ml/culture container), and the lowest density was in treatment C (concentration 300 ml/container). The use of ingredients (POC) derived from coconut water, rice washing water, and chicken egg shells has an effect on the cell density of Chlorella sp. with a p value <0.05). The highest density was on day 10 with a density value of Based on the results obtained from the use of POC as a natural fertilizer for the cultivation of Chlorella sp. For this reason, it is hoped that cultivators need to use POC in the surrounding environment as an alternative fertilizer to replace chemical fertilizers because it has good nutritional content for the Chlorella sp cultivation process and does not pollute the aquatic environment.